Comparison of the Case Development of Serious Human Rights Violations in Indonesia - Anggaretno, Setyaning Wida Nurul (Semarang State University Undergraduate Law and Society Review, 2023)
This paper presents a comparative analysis of the development of legal cases related to serious human rights violations in Indonesia. Despite Indonesia’s commitment to international human rights standards, serious violations, including gross human rights abuses during political conflicts, environmental disasters, and other state-sponsored violations, have been prevalent in its history. These violations, such as the 1965-1966 anti-communist purge, the 1998 reformasi riots, and ongoing issues in Papua, have drawn significant attention from both domestic and international human rights organizations. The study compares the legal processes, outcomes, and the role of national and international bodies in addressing these violations. Key cases such as the 1998 riots and the abuses in East Timor are examined to evaluate Indonesia’s judicial accountability, the involvement of civil society, and the effectiveness of transitional justice mechanisms. Despite the existence of human rights laws and institutions such as the National Human Rights Commission (Komnas HAM) and the Human Rights Court, accountability for these crimes has often been limited, with few perpetrators being prosecuted or convicted. The paper also analyzes the political and social challenges that hinder the progress of human rights cases, including political will, institutional weaknesses, and the influence of the military in decision-making processes. By comparing these cases, the paper highlights the systemic issues that prevent meaningful justice and proposes recommendations for strengthening the legal framework to ensure accountability for serious human rights violations in Indonesia. This comparative study is crucial in understanding the broader implications of human rights protection in the country’s future development.